2016
DOI: 10.5206/cie-eci.v45i2.9289
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the Japan Connection: The Impact of Study Abroad on Japanese Language Learners’ Life Trajectories and Ongoing Interaction with Japanese Speakers

Abstract: This article explores the post-study abroad life trajectories of learners of Japanese. Drawing upon data collected from eight interviewees, it presents the experiences of study abroad returnees’ ongoing engagement with Japan and Japanese speakers once they were removed from the study abroad environment. In particular, it focuses on the impact of study abroad on ongoing studies and career trajectory, and examines ongoing interaction with Japanese speakers throughout these key life stages. Through the lens of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…More pertinent, however, to the present study and the research direction identified by Plews (2016) is recent research on the wider consequences poststudy abroad. Studying in Japan was found to present a "critical incident" in life trajectories (Campbell, 2016), with post-sojourners remaining connected with the country in different ways. Interviews were conducted six months to 15 years after completion of study abroad (all bar one of the eight participants were still students).…”
Section: The Post-study Abroad Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…More pertinent, however, to the present study and the research direction identified by Plews (2016) is recent research on the wider consequences poststudy abroad. Studying in Japan was found to present a "critical incident" in life trajectories (Campbell, 2016), with post-sojourners remaining connected with the country in different ways. Interviews were conducted six months to 15 years after completion of study abroad (all bar one of the eight participants were still students).…”
Section: The Post-study Abroad Contextmentioning
confidence: 99%
“…What the studies reviewed in this section have in common is a consideration, at least in part, of the impact of and upon an L2 in the postsojourn period, arguably in the period beyond immediate re-entry. Save for one participant in Campbell (2016), the participants were still students or had just completed their studies or were on interim internships within their study program. However, a recent study has focused on 33 Anglophone language specialist graduates (French or German) and investigated their career pathways and language identity claimed.…”
Section: The Post-study Abroad Contextmentioning
confidence: 99%